ANALISIS KESALAHAN PESERTA DIDIK KELAS VIII SMP NEGERI 3 PAYAKUMBUH DALAM MENYELESAIKAN SOAL-SOAL MATEMATIKA BERDASARKAN KATEGORI ANALISIS KESALAHAN NEWMAN - Mutiara Jannatul Fitri (Departemen Matematika, 2020)
The purpose of this study was to determine the mistakes of students in solving math problems and describe the factors that cause them. This type of research is a descriptive study with the research subject being students of class VIII.5 SMP Negeri 3 Payakumbuh. Test analysis using Newman's error analysis. The results of the analysis showed that the most errors made by students were errors in writing the final answer with a percentage of 28.92%. The mistakes made by students were not being able to write down the context of the problem correctly, not formulating the known and asked questions correctly, not using formulas and methods, wrong in doing calculations and wrong in writing the final answer. The factors that cause students to make mistakes are low talent, students do not focus when learning, do not understand the material, do not understand the prerequisite material, lack of practice with different questions, and lack of motivation from parents. Keywords__Error Analysis, Mathematical Problems, Newman Error Analysis.